EVALUASI DAN RANCANG ULANG TAMPILAN ANTARMUKA WEBSITE MENGGUNAKAN METODE SYSTEM USABILITY SCALE DAN DESIGN THINKING - Wibowo, I Kadek Tribuana Tungga; Pratama, I Putu Agus Eka (Universitas Nusa Cendana, 2023)
The Communication and Informatics Agency of Gianyar Regency is responsible for providing information and services to the public through their official website. However, as with many organizations, they are faced with the challenge of ensuring optimal usability and quality of user experience. In this study, a usability evaluation of the official website of the Communication and Information Technology Office of Gianyar Regency was conducted using the System Usability Scale (SUS) method. The evaluation results show that their current website has a low level of usability with an average score of 45.28 (grade scale F). Furthermore, these results are used as a reference to provide a solution design to the problems faced using the Design Thinking approach. After that, testing the solution design that has been given to improve the website interface. The test results showed a significant improvement in usability, with an average score of 88.78 (grade scale A). This shows that the improvements and design changes that have been implemented have successfully improved the user experience and usability of the website of the Communication and Information Agency of Gianyar Regency.